Evaluasi Desain User Interface Website Perpustakaan Sekolah dengan Metode Heuristik - Jamilah, Asyfiya Qurratal; Zulaikha, Sri Rohyanti (Nusantara Journal of Information and Library Studies (N-JILS), 2024)
This research aims to evaluate the user interface design of the Al-Bayan Superior Islamic Boarding School (PU) Library website using a heuristic method. This evaluation includes analysis of navigation, visual appearance, accessibility and ease of use. The heuristic method used involves ten design principles proposed by Jacob Nielsen to identify problems in the user interface and provide recommendations for improvement. The research results show that the Al-Bayan library website has several positive aspects such as direct feedback, easy-to-understand language, and an aesthetic minimalist design. Although there are still some things that need improvement such as improving the consistency of visual feedback, form validation to prevent input errors, and improving submenu accessibility. It is hoped that these recommendations will help library managers improve the user experience and better support the student learning process through easier and more efficient access to information. Keyword: heuristic evaluation, user interface design, library website, user experience   ABSTRAK Penelitian ini bertujuan untuk mengevaluasi desain user interface website Perpustakaan SMA Pesantren Unggulan (PU) Al-Bayan menggunakan metode heuristik. Evaluasi ini mencakup analisis terhadap navigasi, tampilan visual, aksesibilitas, serta kemudahan penggunaan. Metode heuristik yang digunakan melibatkan sepuluh prinsip desain yang diusulkan Jacob Nielsen untuk mengidentifikasi masalah dalam user interface dan memberikan rekomendasi perbaikan. Hasil penelitian menunjukkan bahwa website perpustakaan Al-Bayan memiliki beberapa aspek positif seperti umpan balik langsung, bahasa yang mudah dipahami, dan desain minimalis yang estetis. Meskipun masih ada beberapa hal yang perlu diperbaiki seperti meningkatkan konsistensi umpan balik visual, validasi formulir untuk mencegah kesalahan input, dan peningkatan aksesibilitas submenu. Diharapkan rekomendasi ini akan membantu pengelola perpustakaan meningkatkan pengalaman pengguna dan mendukung proses pembelajaran siswa dengan lebih baik melalui akses informasi yang lebih mudah dan efisien.